Exploring Opportunities for Augmenting Homes to Support Exercising - Adiwangsa, M.; Sweetser, P.; Stevenson, D.; Suominen, H.; Xi, M. (United States, 2025)
Although exercising at home has benefts, it is not always engaging or motivating. Augmented Reality (AR) head-mounted displays (HMDs) ofer the potential to make in-home exercising and exergaming more inclusive and immersive, but there is limited research investigating how such systems can be designed. We employed a participatory design approach involving semi-structured interviews to investigate how homes can be augmented to facilitate exercising experiences. We developed 10 recommendations for developing home-based exercising experiences using AR HMDs. Our results further contribute to the existing body of research on the use of AR for exercising, home applications, and everyday objects by presenting the frst foundational study investigating the wide range of exercises that can be supported through AR HMDs in home environments and the diferent ways home elements may support these exercises, and laying the groundwork for future work developing home-based exergaming through AR HMDs to increase people's physical activity levels. © 2024 Copyright held by the owner/author(s)
CHI '24: Proceedings of the CHI Conference on Human Factors in Computing Systems